Analysis of Eswatini Senior Secondary School SiSwati Teachers' Inclusive Education Practice - Mkhonta-Khoza, Portia P.; Dlamini, Nonhlanhla A. (Journal of Education and Practice, 2022)
Purpose: Inclusive education entails children's rights to education in spite of all; it implies that teachers align instruction alongside inclusivity. This study sought to analyze senior secondary school siSwati teachers' inclusive education practice, a case study of schools in the Shiselweni region, Nhlangano cluster. Its objectives were; to ascertain senior secondary school siSwati teacher's views about inclusive education practice; to determine senior secondary school siSwati teachers' implementation of inclusive education practice and to ascertain the challenges of inclusive education practice faced by senior secondary school siSwati teachers. Methodology: The study employed the qualitative approach, blended semi- structured interviews, and document analysis as data collection instruments. A five (5) item semi-structured online interview guide and a document analyses guide with six (6) items designed by the researchers were used for data collection. Purposive sampling was used to select three (3) schools, six (6) teachers were used as participants. Data was analyzed using content analysis. Findings: Findings revealed that teachers lack knowledge on inclusive education; inclusive education strategies were used with separate lessons; shortage of inclusive education resources and the broad siSwati curriculum are major challenges. Unique Contribution to Theory, Policy and Practice: It was concluded that teachers hold negative views towards inclusive education; use inclusive education strategies partially; unavailability of resources and the diversity of the siSwati syllabus are major challenges. It is recommended that teachers get capacitated; siSwati language and literature be taught as separate subjects and government provides inclusive education infrastructure.